Mediation: plea bargaining in criminal cases - Kamarudin, Abdul Rani (CLJ Publication, 2020)
Although mediation is not uncommon when negotiating dispute settlement in civil cases, the same may not necessarily be appropriate with criminal cases — partly because criminal cases pertain to public rights not private rights and any attempt to mediate may fall foul of public interest, hence non-negotiable. In criminal ases, the prosecution, the moment they prefer a charge against any person, they would without doubt seek for a conviction by first establishing a prima facie case, otherwise the accused would not have to enter upon his defence. For the accused, if called upon to enter upon his defence, he would attempt to create reasonable doubt in the prosecution’s case. If he succeeds, the outcome would most likely be an acquittal as the prosecution case may not be proven on a criminal standard of proof, i.e. beyond all reasonable doubt. The Public Prosecutor (‘PP’), however, has unfettered discretion to bring an allegation against an offender but he too has discretion at any stage of the trial, whether to add up or reduce the number of charges; to withdraw the case completely; or substitute it with fewer allegations, hence make do with lesser punishment for the convicted offender. Interestingly too, from 2010, there has been a provision for plea bargaining in the Malaysian Criminal Procedure Code (CPC) that the prosecutor and the accused may avail of, prior to commencement of the trial which is distinct and separate from the prosecutor’s power to withdraw the case at any stage of the trial. This paper discusses the meaning of mediation, whether mediation is possible at the plea bargaining stage by analysing the plea bargaining provisions and other provisions in the CPC with relevant decided cases.